Cerimonial universitário: sistematização na Universidade Federal de Santa Maria - Weber, Tânia Regina (2014)
This study was developed in order to propose the ceremonial systematization of solemn events that take place at the Universidade Federal de Santa Maria (UFSM). Bibliographical researches were performed, and questionnaires were send to the Federal Institutions of Higher Education of the South Region and to the main authorities of the UFSM that are directly involved with solemn events. Analyzing the obtained information and based on the experience of the author, a Ceremonial Manual was elaborated, mainly directed to workers involved with institution events. Using a clear and accessible language, the Ceremonial Manual aims at diminishing frequent doubts, explaining basic ceremonial concepts in a simple way that is easily understood. The Ceremonial Manual contains information about table composition, precedence order at the UFSM, speech order, flags, anthems, academic dresses and examples of scripts, standardizing the procedures and contributing to a more harmonic and coherent practice in the ceremonial of solemn events held at the Institution.